Sistem Pendukung Keputusan Pemilihan Atlit Lari Cepat Menggunakan Logika Fuzzy (Studi Kasus: Koni Sumatera Utara) - Muhammad Iskandar Muda (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2021)
In every event such as the National Sports Week (PON), Regional Sports Week (PORDA), and other sports activities, the Indonesian National Sports Committee (KONI) of North Sumatra, always evaluates the results of the athlete's training, to determine which athletes are eligible. ready to take part in these activities or as a basis for recommendations for athlete participation. Furthermore, to determine the final result of the athlete's recommendation so far, it has also been done by counting manually through several stages and not everyone or the coach understands it, and sometimes there are errors in the process. Fuzzy logic is a set theory that can help in resolving the uncertainty of the boundary between one criterion and another that is generated by a cumulative human assessment of something. This theory can be used to help solve the problem of assessing the physical quality of athletes. One solution that can be done to overcome dependence on experts and the uncertainty of the boundary between one criterion and another is using fuzzy logic which is applied in the form of a visual program that can be used in determining the physical quality of athletes. To process physical test data into athlete recommendation data based on their physical quality, a decision support system is needed. namely using fuzzy logic which is applied in the form of a visual program that can be used in determining the physical quality of athletes.